New approach of blending polymeric ionic liquid with polybenzimidazole (PBI) for enhancing physical and electrochemical properties - Rewar, Anita S.; Chaudhari, Harshal D.; Illathvalappil, Rajith; Sreekumar, K.; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2014)
Although the use of ionic liquids (IL) in polymeric membranes is known to elevate the electrochemical performance for proton exchange membrane-based fuel cells (PEMFC), they suffer from drawbacks such as IL drain and lowering in mechanical properties that lead to deterioration in PEMFC performance. To mitigate these issues, we report, for the first time, the use of polymeric ionic liquid (PIL), namely, poly(diallyl dimethyl ammonium trifluoride methane sulphonate) (P[DADMA][TFMS]) to be blended with polybenzimidazole (PBI-I) as a membrane material for PEMFC. PBI-I and (P[DADMA][TFMS]) were chosen because they form miscible blends and are suitable for acid doping as a matrix, which can eventually be used as proton conductor. The structure, miscibility and inter-polymer interactions were studied by infrared (IR) spectroscopy and differential scanning calorimetry (DSC). The increase in proton conduction in comparison to the PBI membranes was observed due to the presence of ionic groups of PILs in blend membranes. With the increase in PIL content, the proton conductivity of the composite membranes gradually increased from 0.04 S cm(-1) for PBI to 0.07 S cm(-1) for the blend membrane at 150 degrees C. The MEAs were fabricated with PBI-I, PBI-PIL15, PBI-PIL25 and PBI-PIL35. Corresponding single cells were successfully tested at temperatures of 160 degrees C. The maximum power density and current density obtained were 515 mW cm(-2) and 1632 mA cm(-2), respectively, for PBI-PIL25-based MEA.

Polybenzimidazole based film forming polymeric ionic liquids: synthesis and effects of cation-anion variation on their physical properties - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Rewar, Anita S.; Kharul, Ulhas K. (Polymer Chemistry, 2014)
Polymeric ionic liquids (PILs) are gaining wide attention due to their tunable properties and applicability in various upcoming areas, including membranes for CO2 separation. The known methodologies yield PILs that are difficult to convert into film form. The present work investigates a synthetic approach for obtaining PILs based on a strong film forming with a fully aromatic rigid backbone while incorporating ionic liquid character in it. Three structurally different polybenzimidazoles (PBI-I, PBI-BuI and ABPBI) were N-quaternized by a methyl group, followed by iodide exchange with various promising anions. The extent of iodide exchange by another anion was high enough (>94% in most cases). Most of the resulting PILs with various anions offer mechanically strong films, with the exception of those based on acetate and benzoate as an anion. Although the base PBI has excellent film forming ability, this result conveyed the role of anion in governing the film forming ability of the PIL. Salient features of this methodology include a fully aromatic polycation backbone, wide structural tunability (by virtue of variation not only of the anion/cation, but also with N-substituent) and introducing two IL characters per repeat unit of a PIL (except for PILs based on ABPBI). Attempted PIL structural variations showed diverse property variations in bulk and surface properties (solvent solubility, contact angle, water sorption, thermal stability, polyelectrolyte behaviour, CO2 sorption and ionic conductivity). Mechanical properties of film forming PILs exhibited high enough tensile strength, conveying their applicability as membrane materials.

Polybenzimidazole based polymeric ionic liquids (PILs): effects of controlled degree of N-quaternization on physical and gas permeation properties - Rewar, Anita S.; Bhavsar, Rupesh S.; Sreekumar, K.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric ionic liquids (PILs) are gaining increasing attention as potential membrane materials to be employed for CO2 separation. With a goal to improve gas permeability, this work presents a series of film forming PlLs obtained by controlled degree of N-quaternization (DQ) of PBI-BuI using a bulky 4-tertbutylbenzyl group. Concurrent effects of variation in ionic content and bulky group substitution were analyzed for physical and gas permeation properties of the resulting PILs. Attempted structural variations leading to simultaneous increments in ionic content and bulky groups offered amorphous polymers with acceptable thermal stability and non-monotonous chain packing density. Enhancement in pure gas permeability coupled with appreciable selectivity for various gas pairs was in accordance with the packing density variations in the series. Gas permeability showed maxima at DQ of just 13%. This conveyed that effects of bulky group substitution in retarding chain packing are overcome by attractive ionic interactions at much lower DQ in these PILs ionic interactions are thus more predominant in governing chain packing and gas permeation properties. These PILs possessed 3.3-20 times higher CO2 permeability in comparison to their parent PBI-BuI, without a significant loss in selectivity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Degree of quaternization; Gas permeation; Polybenzimidazole; Polymeric ionic liquid

Incorporation of rigid polyaromatic groups in polybenzimidazole-based polymeric ionic liquids: assertive effects on gas permeation properties - Shaligram, Sayali V.; Rewar, Anita S.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Polymer, 2016)
Polymeric ionic liquids (PILs) have emerged as promising membrane materials for CO2 separation. The present work is aimed at investigating the effects of incorporation of rigid polyaromatic hydrocarbons, viz., pyrene and anthracene, in polybenzimidazole-based PILs. The effects of substituent and anion variation on the gas permeation properties of PILs using pure gases were examined at 20 atm upstream pressure. The results were correlated with physical properties of PILs. The pyrene substituted PIL exhibited similar to 10 fold increase in CO2 permeability as compared to its precursor polymer PBI-BuI. The combination of a CO2 specific anion and bulky group substitution offered higher CO2 permeability as well as appreciable permselectivity than their structural analogue that was devoid of IL functionality. The permeation properties of present PILs were superior to those of conventional glassy polymers such as polysulfone, matrimid and polycarbonate which are widely studied for their gas permeation properties. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gas permeation; membranes; Polymeric ionic liquids

Polybenzimidazole based polymeric ionic liquids possessing partial ionic character: effects of anion exchange on their gas permeation properties - Rewar, Anita S.; Shaligram, Sayali V.; Kharul, Ulhas K. (Journal of Membrane Science, 2016)
Polymeric ionic liquids (PILs) are emerging as promising membrane materials for CO2 separation. Present work is in continuation with our earlier efforts on evaluating gas permeation properties (especially, CO2) of film forming PILs based on polybenzimidazoles and efforts towards improving their permeability by structural tuning. This work specifically aims at evaluating effect of anion variation in chosen PILs possessing partial N-quaternization of imidazole moiety of PBI-Bul. Three anions (viz., Tf2N-, BF4- and Ac-) were chosen for the bromide exchange of two PILs, viz., [TBzPBI-Bul][Br](10) and [TBzPBI-Bul][Br](18), possessing degree of PEI N-quaternization (DQ) as 10 and 18%, respectively. Concurrent effects of variation in anion and DQ were analyzed in terms of physical and gas permeation properties of the resulting PILs. All of them possessed amorphous nature, adequate thermal stability ( >= 250 degrees C) and solvent solubility, which are primary requisites towards their applicability as a membrane material. PILs possessing BF4- anion exhibited improved CO2 permeability coefficient as well as its permselectivity over CH4 and N-2, in comparison to their counterparts with other anions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; Gas separation; Polybenzimidazole; Polymeric ionic liquids (PILs)